Participation of teenagers with vision or motor impairments in leisure activities: a qualitative study - Veldhorst, Carlijn; Wijnen, Marjolein; Kef, Sabina; Vervloed, Mathijs P. J.; Steenbergen, Bert (Frontiers in Rehabilitation Sciences, 2024)
PurposeParticipation in everyday life activities is important for the development of children and is an important topic in rehabilitation practices. This qualitative study aimed to unveil the perspectives and experiences of teenagers with vision impairments (VIs) or motor impairments (MIs) regarding their participation in leisure activities.Materials and methods13 teenagers with VIs and 12 teenagers with MIs (age range: 11–15 years) participated in this study. Data were collected using semi-structured interviews. Verbatim transcripts were analyzed following the steps of the phenomenological approach.ResultsA total of 623 significant statements were identified and assigned to 221 meaning units. Finally, 13 themes emerged. Teenagers with VIs and MIs shared many experiences and perspectives regarding participation in leisure activities.ConclusionsTeenagers reported that they can sufficiently indicate what they experience as pleasant and sufficient considering their participation, as well as the challenges they encountered, such as their impairment, limited transport possibilities, or concerns from parents. Overall, teenagers with VIs or MIs were generally satisfied with the degree and frequency of their participation in leisure activities and felt sufficiently involved.